Revealing the Impacts of Climate Change on Peri-Urban Agriculture and Vegetation Cover in Dar es Salaam City, Tanzania (Tanzania Journal for Population studies and Development, 2015)
Agriculture practiced in urban and peri-urban zones is vital for food supply in the Dar es Salaam city, which hosted almost 5 million people in 2015. More than 90% of urban agriculture in the city is leafy vegetables coming from open spaces and home gardens. Extreme climatic changes in terms of rainfall and temperature beyond the normal experience have adversely affected peri-urban agricultural productivity and vegetation cover in the city. This paper provides ample evidence that the natural resource base to feed the urban population is beyond the municipal boundary. The aim of peri-urban agriculture, as reported by most (95%) of the households surveyed in the study, is to ensure food security at household level. The destruction of poor urban gardens, vegetation, property and loss of livelihoods are the common features of urban agriculture due to excessive rains and poor mitigation measures practiced by most of poor urban dwellers that depend solely on land resources. Most urban dwellers (87%) are migrants from rural Tanzania, and thus there is a need to integrate traditional and modern agricultural practices so as to improve farm productivity, vegetation cover and climatic dynamic challenges through adaptation of best practices and learning by doing. Despite the increased attention to and improved understanding of peri-urban agriculture in past two decades, more knowledge is needed to prepare for and manage the urban community risks associated with climate and weather variations in rapidly growing cities like Dar es Salaam.